2019
DOI: 10.1021/acschembio.9b00432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PEGylation on the Strength of Protein Surface Salt Bridges

Abstract: Conjugation of polyethylene glycol (PEGylation) is a well-known strategy for extending the serum half-life of protein drugs and for increasing their resistance to proteolysis and aggregation. We previously showed that PEGylation can increase protein conformational stability; the extent of PEG-based stabilization depends on the PEGylation site, the structure of the PEG−protein linker, and the ability of PEG to release water molecules from the surrounding protein surface to the bulk solvent. The strength of a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…WW variants AA and pAA were synthesized previously . WW variants AL , LA , LL , AF , FA , FF , XA , AX , XX , XL , FL , and LF were prepared as the C-terminal acids via Fmoc-based solid-phase peptide synthesis on Fmoc-Gly-Wang resin (EMD Biosciences) as described previously. ,, Fmoc-protected amino acids with acid-labile side-chain protecting groups were purchased from Advanced ChemTech and used without further purification; we also used previously synthesized N -[(9 H -fluoren-9-ylmethoxy)- O -2-propyn-1yl- l -tyrosine. , Coupling reactions were carried out using 5 equiv of the appropriate Fmoc-protected amino acid, 5 equiv of 2-(1 H -benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate, 5 equiv of N -hydroxybenzotriazole hydrate, and 10 equiv of N , N -diisopropylethylamine in N -methyl-2-pyrrolidinone. Fmoc deprotection reactions were carried out using 20% piperidine in N , N -dimethylformamide.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…WW variants AA and pAA were synthesized previously . WW variants AL , LA , LL , AF , FA , FF , XA , AX , XX , XL , FL , and LF were prepared as the C-terminal acids via Fmoc-based solid-phase peptide synthesis on Fmoc-Gly-Wang resin (EMD Biosciences) as described previously. ,, Fmoc-protected amino acids with acid-labile side-chain protecting groups were purchased from Advanced ChemTech and used without further purification; we also used previously synthesized N -[(9 H -fluoren-9-ylmethoxy)- O -2-propyn-1yl- l -tyrosine. , Coupling reactions were carried out using 5 equiv of the appropriate Fmoc-protected amino acid, 5 equiv of 2-(1 H -benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate, 5 equiv of N -hydroxybenzotriazole hydrate, and 10 equiv of N , N -diisopropylethylamine in N -methyl-2-pyrrolidinone. Fmoc deprotection reactions were carried out using 20% piperidine in N , N -dimethylformamide.…”
Section: Methodsmentioning
confidence: 99%
“…The desolvation and burial of nonpolar residues in the interior of protein tertiary and quaternary structures provides a major driving force for protein folding via enthalpic and entropic contributions known collectively as the hydrophobic effect. This process allows the ordered water molecules that surrounded the nonpolar residues in the unfolded conformation to be released to bulk solvent upon folding; it also maximizes the contact surface area between nonpolar side chains in the folded conformation. Previous observations suggest that side-chain PEGylation similarly releases surface-bound water molecules in the immediate vicinity of the PEGylation site, thereby increasing protein conformational stability via an entropic effect. , We recently found that the strength of a salt bridge between Glu12 and Arg14 in the WW domain (hereafter called WW) increases when a propargyloxyphenylalanine residue at position 23 (PrF23) is modified with a PEG-azide via the copper-catalyzed azide–alkyne cycloaddition (compare ER vs pER in Table ; Figure ). We chose WW as a model protein because its two-state folding energetics have been extensively characterized because it is relatively tolerant to amino acid substitutions at many locations and because its short length (34 residues) facilitates its preparation via solid-phase peptide synthesis, making it much easier to install a short PEG oligomer at a single well-defined location. , Presumably the PEGylated PrF residue (PrFp23) in WW strengthens the nearby Glu12–Arg14 salt bridge by shielding it from interfering water molecules.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, buried hydrogen bonds are strengthened by their nonpolar microenvironment , presumably due to the lower effective dielectric constant of the protein interior versus the surface and the absence of interfering water molecules. Similarly, a growing body of experimental and theoretical evidence suggests that attaching polyethylene glycol to a protein side chain (i.e., PEGylation) can strengthen nearby noncovalent interactions by localized desolvation of the area immediately surrounding the PEGylation site. ,, We previously found that conjugating a four-unit PEG oligomer to the side-chain amide nitrogen of Asn26 increases the conformational stability of PEGylated WW variant WNp by −0.58 ± 0.06 kcal/mol relative to its non-PEGylated counterpart, WN (Figure A) . Analysis of solvent radial gradient distribution functions derived from previous atomistic simulations of WN and WNp in explicit water suggested that fewer water molecules surround Trp11 in PEGylated WNp than in non-PEGylated WN (Figure A); this suggestion is consistent with our observations that the increased stability of WNp relative to WN comes from a favorable entropic term (− T ΔΔ S = −3.8 ± 0.5 kcal/mol) offset by an unfavorable enthalpic term (ΔΔ H = 3.2 ± 0.5 kcal/mol) .…”
mentioning
confidence: 98%